PROFESSIONALISM OF EARLY CHILDHOOD EDUCATOR TO SUPPORT INDUSTRIAL REVOLUTION 4.0 BASED ON LOCAL CULTURE - Intan Prastihastari; Anik Lestariningrum (Universitas Muhammadiyah Ponorogo, 2019)
Professional educators are expected to be one of the efforts to realize quality human resources, especially towards the industrial revolution 4.0. However, the concept of professionalism, especially for early childhood educators, has very complex coverage especially with regard to the characteristics of their students and the competencies that educators must possess. Local culture based early childhood education is expected to be an effort to implement educator competencies where later the role that is raised will still maintain the peculiarities of early childhood education by not forgetting the preparation of students to recognize technology as one component in the 4.0 industrial revolution. Changes to this will be done by educators by first preparing their students in accordance with the conditions of their respective socio-cultural environment so that the concepts that children have remain meaningful in accordance with the stages of child development. This qualitative descriptive research method was carried out in TK Negeri Pembina Kediri City with a group B research object, the results of local culture-based development activities can be obtained if the professionalism of educators continues to be improved especially in handling according to revolution 4.0. The results obtained are the implementation that has been carried out by TK Negeri Pembina Kota Kediri through the development of themes that contain local culture, innovation required by teachers to master technology.